Use of a Conditional Ubr5 Mutant Allele to Investigate the Role of an N-End Rule Ubiquitin-Protein Ligase in Hedgehog Signalling and Embryonic Limb Development. - Elaine Kinsella; Natalie Dora; David Mellis; Laura Lettice; Paul Deveney; Robert Hill; Mark Ditzel (PLoS ONE)
Hedgehog (Hh) signalling is a potent regulator of cell fate and function. While much is known about the events within a Hh-stimulated cell, far less is known about the regulation of Hh-ligand production. Drosophila Hyperplastic Discs (Hyd), a ubiquitin-protein ligase, represents one of the few non-transcription factors that independently regulates both hh mRNA expression and pathway activity. Using a murine embryonic stem cell system, we revealed that shRNAi of the mammalian homologue of hyd, Ubr5, effectively prevented retinoic-acid-induced Sonic hedgehog (Shh) expression. We next investigated the UBR5:Hh signalling relationship in vivo by generating and validating a mouse bearing a conditional Ubr5 loss-of-function allele. Conditionally deleting Ubr5 in the early embryonic limb-bud mesenchyme resulted in a transient decrease in Indian hedgehog ligand expression and decreased Hh pathway activity, around E13.5. Although Ubr5-deficient limbs and digits were, on average, shorter than control limbs, the effects were not statistically significant. Hence, while loss of UBR5 perturbed Hedgehog signalling in the developing limb, there were no obvious morphological defects. In summary, we report the first conditional Ubr5 mutant mouse and provide evidence for a role for UBR5 in influencing Hh signalling, but are uncertain to whether the effects on Hedgehog signaling were direct (cell autonomous) or indirect (non-cell-autonomous). Elaboration of the cellular/molecular mechanism(s) involved may help our understanding on diseases and developmental disorders associated with aberrant Hh signalling.